The Effect of Work-Life Balance, Product Branding, and Use of Fintech Technology on Operational Efficiency of Start-ups in Yogyakarta - Mei Rani Amalia; Rika Desiyanti; Rully Fildansyah (Westscience Press, 2024)
This study examines the effects of work-life balance, product branding, and fintech technology on the operational efficiency of start-up companies in Yogyakarta. A quantitative approach was employed, with data collected from 80 respondents using a structured questionnaire and analyzed with SPSS version 26. The results indicate that all three variables have significant positive effects on operational efficiency. Product branding had the strongest impact, followed by fintech technology and work-life balance. The findings suggest that start-up managers can enhance operational performance by prioritizing employee well-being, investing in effective branding strategies, and adopting fintech solutions. These insights contribute to the understanding of key drivers of operational efficiency in the start-up ecosystem and offer practical implications for improving start-up sustainability.